Belleza Beauty & Health / Anis Izzati Ramli … [et al.] - Ramli, Anis Izzati; Syukri, Muhammad Faris Syazwi; Ahmad Tamizi, Nur Awatif; Mohamad Zainuddin, Nur Syafinie; Ramli, Nur Syakirah (2022)
This case study provides a background of the company as well as an analysis of the company's sales performance. The owner of Belleza Beauty and Health is a partnership business and focused on selling a variety of products that consist of beauty, health and also DIY repairing products. The brand Belleza Beauty & Health and now known as Erisyaa Cosmetics is operated in small shops located at Taman Tasik Prima, Puchong. This case study also discusses the problem that Belleza Beauty and Health is experiencing, as well as the solutions to the problem. The method used to study the case is using primary sources which refer to data which does not exist created by researchers who collect it through surveys, interviews, experiments and observations. We collect the information through interviews with the owner of the company and observation as one of the customers of the company. We also employed secondary data, such as web research. We are able to prepare the company's Business Model Canvas through data collecting, which is crucial because it is a strategic management tool that allows us to conceive and assess the business idea or concept. It illustrates the strength of the organization, which provides a variety of products that consist of beauty, health and DIY repairing products. This also demonstrates particular pathways to be developed for the organization's future strategy. The result from the data that had been collected shows that Belleza Beauty and Health still could improve their sales performance by solving the problems. This will result in a rise in the number of loyal customers for the firm. The case study finds that the company had faced many problems regarding their low attraction due to many competitors and decline in sales during Covid-19 outbreak. The significant weakness necessitated modifications and fast action by management. There are recommendations in this case study for the best solution that the organization could implement. This case study also looks at the fact that the analysis is limited. One of the constraints is that the corporation must find another solution to its challenge.